Local mechanisms for loud sound-enhanced aminoglycoside entry into outer hair cells - Li, Hongzhe; Kachelmeier, Allan; Furness, David N.; Steyger, Peter S. (Frontiers in Cellular Neuroscience, 2015)
Loud sound exposure exacerbates aminoglycoside ototoxicity, increasing the risk of permanent hearing loss and degrading the quality of life in affected individuals. We previously reported that loud sound exposure induces temporary threshold shifts (TTS) and enhances uptake of aminoglycosides, like gentamicin, by cochlear outer hair cells (OHCs). Here, we explore mechanisms by which loud sound exposure and TTS could increase aminoglycoside uptake by OHCs that may underlie this form of ototoxic synergy. Mice were exposed to loud sound levels to induce TTS, and received fluorescently-tagged gentamicin (GTTR) for 30 min prior to fixation. The degree of TTS was assessed by comparing auditory brainstem responses (ABRs) before and after loud sound exposure. The number of tip links, which gate the GTTR-permeant mechanoelectrical transducer (MET) channels, was determined in OHC bundles, with or without exposure to loud sound, using scanning electron microscopy. We found wide-band noise (WBN) levels that induce TTS also enhance OHC uptake of GTTR compared to OHCs in control cochleae. In cochlear regions with TTS, the increase in OHC uptake of GTTR was significantly greater than in adjacent pillar cells. In control mice, we identified stereociliary tip links at ~50% of potential positions in OHC bundles. However, the number of OHC tip links was significantly reduced in mice that received WBN at levels capable of inducing TTS. These data suggest that GTTR uptake by OHCs during TTS occurs by increased permeation of surviving, mechanically-gated MET channels, and/or non-MET aminoglycoside-permeant channels activated following loud sound exposure. Loss of tip links would hyperpolarize hair cells and potentially increase drug uptake via aminoglycoside-permeant channels expressed by hair cells. The effect of TTS on aminoglycoside-permeant channel kinetics will shed new light on the mechanisms of loud sound-enhanced aminoglycoside uptake, and consequently on ototoxic synergy.